Pengaruh Pemberian Pupuk Kompos Ampas Tebu Terhadap Pertumbuhan Dan Hasil Tanaman Jagung Manis (Zea mays saccaratha Sturt) - Juhair Arifin; Edward Bahar; Rizah Rizwana Wahyuni (Fakultas Pertanian Universitas Ratu Samban, 2025)
Sweet Corn (Zea mays saccaratha Sturt) is in great demand because of its nutritional and economic value. Sweet corn consumption is increasing in Indonesia, but the industry faces challenges such as pests, disease and access to fertilizer. Using sugarcane bagasse as compost can increase soil fertility and reduce waste. This research aims to determine the effect of the dose of bagasse compost on the growth and yield of sweet corn. This research used a Randomized Block Design (RAK) with 5 actions, namely P0 : without adding bagasse compost (control), P1: 20 tons/ha of bagasse compost equivalent to 1.96 kg/plot, P2 : 25 tons/ha of bagasse compost equivalent to 2.45 kg/plot, P3: 30 tons/ha of bagasse compost equivalent to 2.94 kg/plot, P4: 35 tons/ha of bagasse compost equivalent to 3.43 kg/plot Each treatment was repeated four times in groups. The variables observed were plant height, leaf length, leaf width, cobs length, cobs diameter and cobs weight. The results of data analysis are analyzed using variance analysis, if the results of variance analysis show a real difference, then proceed with a further significant difference test (DMRT 5%). The results of the research showed that the provision of bagasse compost did not have a real effect on any observed variables. The absence of real differences in all observed variables is thought to be caused by the dosage of bagasse compost not having reached the right level to support optimal growth in sweet corn plants.